Moving Beyond Salmon Bias: Mexican Return Migration and Health Selection - Diaz, Christina J. (Demography, 2016)
Despite having lower levels of education and limited access to health care services, Mexican immigrants report better health outcomes than U.S.-born individuals. Research suggests that the Mexican health advantage may be partially attributable to selective return migration among less healthy migrants—often referred to as “salmon bias.” Our study takes advantage of a rare opportunity to observe the health status of Mexican-origin males as they cross the Mexican border. To assess whether unhealthy migrants are disproportionately represented among those who return, we use data from two California-based studies: the California Health Interview Survey; and the Migrante Study, a survey that samples Mexican migrants entering and leaving the United States through Tijuana. We pool these data sources to look for evidence of health-related return migration. Results provide mixed support for salmon bias. Although migrants who report health limitations and frequent stress are more likely to return, we find little evidence that chronic conditions and self-reported health are associated with higher probabilities of return. Results also provide some indication that limited health care access increases the likelihood of return among the least healthy. This study provides new theoretical considerations of return migration and further elucidates the relationship between health and migration decisions.